A recycled concrete with self-repairing properties
The regenerated aggregate is modified by heteropolyacid and phosphomolybdate to form reversible bonded modified aggregate, which solves the problem of prone to cracking of regenerated concrete and achieves the improvement of self-repair and tensile resistance.
Patent Information
- Application Number
- CN202311855124.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-12-29
AI Technical Summary
Recycled concrete is prone to cracking due to its high water absorption rate and poor interfacial adhesion force, resulting in a decrease in structural durability.
The regenerated aggregate is modified by heteropolyacid and phosphomolybdate to form reversible bonded modified aggregates, giving the regenerated concrete self-repairing properties. When regenerated concrete cracks, the modified aggregates are self-repaired by reversible bonding.
Recycled concrete can be self-repaired after cracking, improving the durability and tensile resistance of the structure.
Smart Images

Figure BDA0004642006060000011 
Figure BDA0004642006060000061 
Figure BDA0004642006060000062
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of recycled concrete, and in particular, relates to recycled concrete with self-repairing properties. Background Art
[0002] Crushing and processing abandoned concrete and bricks from construction solid waste into recycled aggregates, and using recycled aggregates to prepare recycled concrete can not only solve the problem of shortage of natural sand and gravel resources, but also effectively solve the problem of construction waste stacking and pollution, which has important practical significance. Because there are some old cement mortars attached to the surface of recycled aggregates, and there are a large number of cracks on the surface and inside due to damage accumulation during the crushing production process, compared with natural aggregates, recycled aggregates have disadvantages such as low density, high water absorption, and poor interface adhesion. Therefore, its workability and mechanical properties are significantly lower than those of ordinary concrete. During service, due to its high water absorption and poor interface adhesion, it is easy to crack, causing some corrosive ions to penetrate, resulting in a significant reduction in the durability of the concrete structure. Summary of the invention
[0003] The object of the present invention is to provide a recycled concrete with self-repairing properties, which can achieve self-repair after cracking during service.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A recycled concrete with self-repairing properties, comprising the following raw materials in parts by weight:
[0006]
[0007] Wherein: the particle size range of the natural aggregate is 5 to 10 mm; the modified aggregate is obtained by modifying the recycled aggregate with heteropoly acid and phosphomolybdic acid, and the particle size range is 5 to 15 mm.
[0008] As a preferred embodiment of the present invention, the modified aggregate is prepared by the following method: adding recycled aggregate to a heteropoly acid modifier, soaking at a constant temperature for 24 to 36 hours, and air-drying;
[0009] The heteropoly acid modifier is prepared by the following method: heating and dissolving the phosphomolybdic acid functionalized polyionic liquid in N,N-dimethylformamide to obtain a first solution, and adding H3PW 12 O 40 The second solution is obtained by heating and dissolving in N,N-dimethylformamide, heating the first solution and the second solution to 60-65° C., stirring and mixing to obtain a uniform solution.
[0010] As a preferred embodiment of the present invention, the usage ratio of the phosphomolybdic acid functionalized polyionic liquid and N,N-dimethylformamide in the first solution is 1 g: 5-6 mL.
[0011] As a preferred embodiment of the present invention, the H3PW in the second solution 12 O 40 The usage ratio of N,N-dimethylformamide is 0.05~0.1g:3mL.
[0012] As a preferred embodiment of the present invention, the volume ratio of the first solution to the second solution is 1:1.
[0013] As a preferred embodiment of the present invention, the phosphomolybdic acid functionalized polyionic liquid is prepared by the following operations:
[0014] Diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane and n-butyl bromide are placed in a reactor, azobisisobutyronitrile is added for the first time and mixed evenly, and stirred and refluxed at 60-70°C for 1-1.5h, azobisisobutyronitrile is added for the second time, and stirred and refluxed at 75-80°C until viscous, and then diluted with tetrahydrofuran, allowed to stand, and the precipitate is taken and dissolved in excess petroleum ether for 1-3 times, purified, and dried to obtain a brominated ester copolymer;
[0015] The phosphomolybdic acid and bromoester copolymer are added into deionized water and mixed evenly, and stirred at 60-65° C. for 2-4 hours to obtain a solid. The solid is washed with water for 1-3 times, purified, and dried to obtain a phosphomolybdic acid functionalized polyionic liquid.
[0016] As a preferred embodiment of the present invention, the usage ratio of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane, n-butyl bromide and azobisisobutyronitrile added for the first time is 4-5g:1g:8-10mL:0.01-0.05mL:20-25mg.
[0017] As a preferred embodiment of the present invention, the mass of the azobisisobutyronitrile added for the second time is the same as that of the azobisisobutyronitrile added for the first time.
[0018] As a preferred embodiment of the present invention, in the preparation of the solid, the usage ratio of the phosphomolybdic acid, the bromoester copolymer and the deionized water is 4-6 mg:1 mg:3-5 mL.
[0019] Beneficial effects of the present invention:
[0020] The recycled concrete with self-repairing performance provided by the present invention is achieved by modifying the recycled aggregate with heteropoly acid and phosphomolybdic acid. The protons in the phosphomolybdic acid can combine with the oxygen atoms in the heteropoly acid at room temperature to form a coordination bond. This bonding is a reversible bonding reaction. Therefore, when the heteropoly acid and phosphomolybdic acid modify the recycled aggregate at the same time, the recycled aggregate is endowed with the reversible bonding characteristic and has self-repairing performance. When the recycled concrete cracks, the modified aggregate can achieve self-repairing through reversible bonding.
[0021] Furthermore, the heteropoly acid modifier is prepared by compounding heteropoly acid with phosphomolybdic acid functionalized polyionic liquid. The heteropoly acid anion has a large volume, a large mass, and a concentrated charge density. It will undergo violent Brownian motion under an alternating electric field or a magnetic field and conduct heat energy to nearby molecules. On this basis, the microwave responsiveness of the heteropoly acid and the addition of adjustable microwave radiation can complete the self-healing of recycled concrete. The heteropoly acid anion acts as a crosslinking agent, increasing the charge number of the polyacid anion, making the crosslinking points more concentrated, increasing the force conduction when the material is subjected to stress, and enhancing the tensile strength of the recycled concrete. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific implementation methods.
[0023] Example 1
[0024] The heteropolyacid modifier was prepared by performing the following steps:
[0025] 1kg of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane and n-butyl bromide were put into the reactor, azobisisobutyronitrile was added for the first time and mixed evenly, stirred and refluxed at 60°C for 1h, azobisisobutyronitrile was added for the second time, and the mass of azobisisobutyronitrile added for the second time was the same as that of azobisisobutyronitrile added for the first time, stirred and refluxed at 75°C until viscous, and then diluted with tetrahydrofuran, allowed to stand, and the precipitate was taken and dissolved in excess petroleum ether for one time, purified, and dried to obtain a bromoester copolymer. Among them, the amount ratio of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane, n-butyl bromide and azobisisobutyronitrile added for the first time was 4g:1g:8mL:0.01mL:20mg.
[0026] 0.5 kg of phosphomolybdic acid and bromoester copolymer were added to deionized water and mixed evenly, and stirred at 60°C for 2 hours to obtain a solid, which was washed once with water, purified, and dried to obtain a phosphomolybdic acid functionalized polyionic liquid. The amount ratio of phosphomolybdic acid, bromoester copolymer, and deionized water was 4 mg: 1 mg: 3 mL.
[0027] 0.5 kg of phosphomolybdic acid functionalized polyionic liquid was heated and dissolved in N,N-dimethylformamide to obtain a first solution, wherein the amount ratio of phosphomolybdic acid functionalized polyionic liquid to N,N-dimethylformamide was 1 g:5 mL; 0.5 kg of H3PW 12 O 40 Heat and dissolve in N,N-dimethylformamide to obtain the second solution, H3PW 12 O 40The dosage ratio of N,N-dimethylformamide is 0.05 g:3 mL; the first solution and the second solution are heated to 60° C., and stirred and mixed evenly at a volume ratio of 1:1 to obtain a heteropolyacid modifier.
[0028] Example 2
[0029] The heteropolyacid modifier was prepared by performing the following steps:
[0030] 1kg of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane and n-butyl bromide were put into the reactor, azobisisobutyronitrile was added for the first time and mixed evenly, stirred and refluxed at 65°C for 1.2h, azobisisobutyronitrile was added for the second time, and the mass of azobisisobutyronitrile added for the second time was the same as that of azobisisobutyronitrile added for the first time, stirred and refluxed at 78°C until viscous, and then diluted with tetrahydrofuran, allowed to stand, and the precipitate was dissolved in excess petroleum ether for 2 times, purified, and dried to obtain a bromoester copolymer. Among them, the amount ratio of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane, n-butyl bromide and azobisisobutyronitrile added for the first time was 4.5g:1g:9mL:0.03mL:22mg.
[0031] 0.5 kg of phosphomolybdic acid and bromoester copolymer were added to deionized water and mixed evenly, and stirred at 62°C for 3 hours to obtain a solid, which was washed twice with water, purified, and dried to obtain a phosphomolybdic acid functionalized polyionic liquid. The amount ratio of phosphomolybdic acid, bromoester copolymer, and deionized water was 5 mg: 1 mg: 4 mL.
[0032] 0.5 kg of phosphomolybdic acid functionalized polyionic liquid was heated and dissolved in N,N-dimethylformamide to obtain a first solution, wherein the amount ratio of phosphomolybdic acid functionalized polyionic liquid to N,N-dimethylformamide was 1 g:5.5 mL; 0.5 kg of H3PW 12 O 40 Heat and dissolve in N,N-dimethylformamide to obtain the second solution, H3PW 12 O 40 The dosage ratio of N,N-dimethylformamide is 0.08 g:3 mL; the first solution and the second solution are heated to 62° C., and stirred and mixed evenly at a volume ratio of 1:1 to obtain a heteropolyacid modifier.
[0033] Example 3
[0034] The heteropolyacid modifier was prepared by performing the following steps:
[0035] 1kg of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane and n-butyl bromide were put into the reactor, azobisisobutyronitrile was added for the first time and mixed evenly, stirred and refluxed at 70°C for 1.5h, azobisisobutyronitrile was added for the second time, and the mass of azobisisobutyronitrile added for the second time was the same as that of azobisisobutyronitrile added for the first time, stirred and refluxed at 80°C until viscous, and then diluted with tetrahydrofuran, allowed to stand, and the precipitate was taken and dissolved in excess petroleum ether for 3 times, purified, and dried to obtain a brominated ester copolymer. Among them, the amount ratio of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane, n-butyl bromide and azobisisobutyronitrile added for the first time was 5g:1g:10mL:0.05mL:25mg.
[0036] 0.5 kg of phosphomolybdic acid and bromoester copolymer were added to deionized water and mixed evenly, stirred at 65°C for 4 hours to obtain a solid, washed the solid with water 3 times, purified, and dried to obtain a phosphomolybdic acid functionalized polyionic liquid. The amount ratio of phosphomolybdic acid, bromoester copolymer, and deionized water was 6 mg: 1 mg: 5 mL.
[0037] 0.5 kg of phosphomolybdic acid functionalized polyionic liquid was heated and dissolved in N,N-dimethylformamide to obtain a first solution, wherein the amount ratio of phosphomolybdic acid functionalized polyionic liquid to N,N-dimethylformamide was 1 g:6 mL; 0.5 kg of H3PW 12 O 40 Heat and dissolve in N,N-dimethylformamide to obtain the second solution, H3PW 12 O 40 The dosage ratio of N,N-dimethylformamide is 0.1 g:3 mL; the first solution and the second solution are heated to 65° C., and stirred and mixed evenly at a volume ratio of 1:1 to obtain a heteropolyacid modifier.
[0038] Example 4
[0039] Recycled concrete is made from:
[0040]
[0041] The particle size of the natural aggregate is in the range of 5 to 10 mm, the modified aggregate is prepared from recycled aggregate, the particle size of the recycled aggregate is in the range of 5 to 15 mm, and the modified aggregate is prepared by modifying the recycled aggregate with heteropoly acid and phosphomolybdic acid.
[0042] The modification of the recycled aggregate is specifically as follows: adding the recycled aggregate to the heteropolyacid modifier prepared in Example 1, soaking at a constant temperature for 24 hours, and air-drying to obtain the modified aggregate.
[0043] Example 5
[0044] Recycled concrete is made from:
[0045]
[0046] The particle size of the natural aggregate is in the range of 5 to 10 mm, the modified aggregate is prepared from recycled aggregate, the particle size of the recycled aggregate is in the range of 5 to 15 mm, and the modified aggregate is prepared by modifying the recycled aggregate with heteropoly acid and phosphomolybdic acid.
[0047] The modification of the recycled aggregate is specifically as follows: adding the recycled aggregate to the heteropolyacid modifier prepared in Example 2, soaking at a constant temperature for 30 hours, and air-drying to obtain the modified aggregate.
[0048] Example 6
[0049] Recycled concrete is made from:
[0050]
[0051] The particle size of the natural aggregate is in the range of 5 to 10 mm, the modified aggregate is prepared from recycled aggregate, the particle size of the recycled aggregate is in the range of 5 to 15 mm, and the modified aggregate is prepared by modifying the recycled aggregate with heteropoly acid and phosphomolybdic acid.
[0052] The modification of the recycled aggregate is specifically as follows: adding the recycled aggregate to the heteropolyacid modifier prepared in Example 3, soaking at a constant temperature for 36 hours, and air-drying to obtain the modified aggregate.
[0053] Comparative Example 1
[0054] A recycled concrete, compared with Example 6, uses phosphomolybdic acid functionalized polyionic liquid to replace the heteropolyacid modifier of Example 3, and the rest is the same as Example 6.
[0055] Comparative Example 2
[0056] A recycled concrete, compared with Example 6, uses the following modifier to replace the heteropolyacid modifier in Example 3, and the rest is the same as Example 6.
[0057] The modifier is prepared by the following operation: 1 kg of H3PW 12 O 40 Heat to 60-65℃ and dissolve in N,N-dimethylformamide, stir and mix evenly to obtain H3PW 12 O 40 The usage ratio of N,N-dimethylformamide is 0.05~0.1g:3mL.
[0058] The recycled concrete raw materials provided in Examples 4 to 6 and Comparative Examples 1 to 2 were respectively mixed and mixed according to the Chinese standard GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", and a cylindrical mold with a size of φ100mm×100mm was used to cast and mold concrete specimens. The concrete specimens were then demolded and placed in a standard curing room (RH=90%, T=20℃±3℃) for curing for a total of 28 days.
[0059] The recycled concrete samples prepared in the above Examples 4 to 6 and Comparative Examples 1 to 2 were tested as follows:
[0060] Test Example 1 Repair performance test
[0061] The cracks were made in the recycled concrete samples obtained in the above Examples 4 to 6 and Comparative Examples 1 to 2. The specific operation was as follows:
[0062] (1) Clean and dry all surfaces of the cured cylindrical concrete specimens, then wrap two circles of tape around the specimens to prevent the specimens from completely splitting and separating during the splitting process.
[0063] (2) Place the cylindrical concrete specimen wrapped with tape on the pressure testing machine and control the loading speed to between 0.15 kN / s and 0.25 kN / s. Observe the specimen carefully. When visible microcracks appear on its surface, stop loading immediately and remove the specimen.
[0064] (3) Thin steel nails of different diameters are embedded into the microcracks. Cracks of different widths are obtained by controlling the diameter and depth of the steel nails. The crack width is controlled between 0.35 mm and 0.50 mm.
[0065] The self-repairing performance of the cracked recycled concrete specimens was tested. The test method is as follows:
[0066] A high-power camera (D780, Nikon, Japan) was used to take vertical photos of the recycled concrete specimens prepared in Examples 4 to 6 and Comparative Examples 1 to 2 before and after repair. Then, the crack images were binarized using the "Image-J" software. By analyzing the grayscale value of the crack area, its pixel value can be determined. The grayscale threshold was set to 115 to achieve threshold segmentation of the crack area, thereby obtaining images before and after crack repair. The repaired area of the crack was selected for pixel statistics, and finally the area repair rate was calculated according to the ratio of crack area pixels to initial crack pixels after different repair times. The calculation formula is as follows, and the results are shown in Table 1:
[0067]
[0068] In the formula, A Ris the area repair rate, A0 is the pixel value of the initial crack area, A t is the pixel value of the crack area after repairing for time t.
[0069] Table 1
[0070]
[0071]
[0072] It can be seen from Table 1 that the self-repairing recycled concrete provided by Examples 4 to 6 of the present invention has good repair performance, which can reach more than 90%, while in Comparative Example 1, phosphomolybdic acid functionalized polyionic liquid is used instead of the heteropolyacid modifier provided by the present invention, and its area repair rate is only 40.8%. In Comparative Example 2, heteropolyacid is used instead of the heteropolyacid modifier provided by the present invention, and its area repair rate is only 69.7%, which is significantly lower than that of Example 6. It can be seen that after being treated with the heteropolyacid modifier prepared by phosphomolybdic acid and heteropolyacid, the recycled concrete has good self-repairing performance.
[0073] Test Example 2: Tensile Strength Test
[0074] The tensile strength test of the recycled concrete obtained in Examples 4 to 6 and Comparative Examples 1 to 5 was carried out using a fully automatic concrete pressure testing machine with a production number of DYE-2000S produced by Hebei Xinmeite Instrument Equipment Co., Ltd. The load loading speed was set to 0.3 MPa / s, the load speed was 3 KN / s, and the specimen size was 100 mm×100 mm×100 mm. The results are shown in Table 2.
[0075] Table 2
[0076] Experimental Group Tensile strength / MPa Example 4 2.3 Example 5 2.3 Example 6 2.4 Comparative Example 1 1.8 Comparative Example 2 2.0
[0077] It can be seen from Table 1 that the tensile strength of the recycled concrete with self-repairing properties provided by Examples 4 to 6 of the present invention is slightly improved, while in Comparative Example 1, the heteropolyacid modifier provided by the present invention is replaced by a phosphomolybdic acid functionalized polyionic liquid, and its tensile strength is 1.8 MPa. Comparative Example 2 replaces the heteropolyacid modifier provided by the present invention with a heteropolyacid, and its tensile strength is 2.0 MPa, which is slightly lower than that of Example 6. It can be seen that after treatment with the heteropolyacid modifier of the present invention, the tensile strength of the recycled concrete is improved.
[0078] The above is only an implementation method of the invention, and does not limit the scope of patent protection. Those skilled in the art can make non-substantial changes or substitutions based on the invention, which still fall within the scope of patent protection.
Claims
1. A recycled concrete with self-repairing properties, characterized in that: Contains the following raw materials in parts by weight: 500-600 parts of cement; 800-1000 parts of natural aggregate; 600-800 parts of modified aggregate; 3-5 parts of water reducing agent; 100-120 parts of water; Wherein: the particle size range of the natural aggregate is 5 to 10 mm; the particle size range of the modified aggregate is 5 to 15 mm; The modified aggregate is prepared by the following method: adding recycled aggregate to a heteropoly acid modifier, soaking at a constant temperature for 24 to 36 hours, and air-drying; The heteropoly acid modifier is prepared by the following method: heating and dissolving the phosphomolybdic acid functionalized polyionic liquid in N,N-dimethylformamide to obtain a first solution, and adding H3PW 12 O 40 The second solution is obtained by heating and dissolving in N,N-dimethylformamide, heating the first solution and the second solution to 60-65° C., stirring and mixing to obtain a uniform solution.
2. The recycled concrete according to claim 1, characterized in that: The dosage ratio of the phosphomolybdic acid functionalized polyionic liquid and N,N-dimethylformamide in the first solution is 1 g: 5-6 mL.
3. The recycled concrete according to claim 1, characterized in that: The second solution H3PW 12 O 40 The usage ratio of N,N-dimethylformamide is 0.05~0.1g:3mL.
4. The recycled concrete according to claim 1, characterized in that: The volume ratio of the first solution to the second solution is 1:
1.
5. The recycled concrete according to claim 1, characterized in that: The phosphomolybdic acid functionalized polyionic liquid is prepared by the following operations: Diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane and n-butyl bromide are placed in a reactor, azobisisobutyronitrile is added for the first time and mixed evenly, and stirred and refluxed at 60-70°C for 1-1.5h, azobisisobutyronitrile is added for the second time, and stirred and refluxed at 75-80°C until viscous, and then diluted with tetrahydrofuran, allowed to stand, and the precipitate is taken and dissolved in excess petroleum ether for 1-3 times, purified, and dried to obtain a brominated ester copolymer; The phosphomolybdic acid and bromoester copolymer are added into deionized water and mixed evenly, and stirred at 60-65° C. for 2-4 hours to obtain a solid. The solid is washed with water for 1-3 times, purified, and dried to obtain a phosphomolybdic acid functionalized polyionic liquid.
6. The recycled concrete according to claim 5, characterized in that: The usage ratio of diethylaminoethyl methacrylate, methyl acrylate, 1,4-dioxane, n-butyl bromide and azobisisobutyronitrile added for the first time is 4-5g:1g:8-10mL:0.01-0.05mL:20-25mg.
7. The recycled concrete according to claim 5, characterized in that: The mass of azobisisobutyronitrile added for the second time is the same as that of azobisisobutyronitrile added for the first time.
8. The recycled concrete according to claim 5, characterized in that: In the preparation of the solid, the usage ratio of the phosphomolybdic acid, the bromoester copolymer and the deionized water is 4-6 mg: 1 mg: 3-5 mL.
Citation Information
Patent Citations
Heteropolyacid type polyion liquid self-healing material as well as preparation method and application thereof
CN114671972A
Self-repairing recycled concrete and preparation method thereof
CN116514481A